Kampanye Humas Komisi Pemilihan Umum (KPU) RI melalui Film Kejarlah Janji di Kota Tangerang Selatan - Farrah Saphira; Lilik Sumarni (Jurnal Ilmu Komunikasi, Administrasi Publik dan Kebijakan Negara, 2025)
General Elections (Pemilu) are one of the important moments in democratic life in Indonesia. Indonesian elections are a true expression of democracy and a means for the people to declare their sovereignty over the state and government. Elections are based on Pancasila and the 1945 Constitution of the Republic of Indonesia and are held in the Unitary State of the Republic of Indonesia (NKRI) based on the principle of direct, universal, free elections. , confidential, honest and fair Political participation in a democratic country shows that the people fulfill the highest legitimacy of state power (popular sovereignty), this is manifested in the form of participation in democratic political parties (elections) for the welfare of the people. A very interesting group of voters to follow and study Furthermore, novice voters or new voters are voters who are taking part in an election for the first time, especially the millennial generation, who have a crucial role in determining the future direction of the nation. This research aims to explore the understanding and perceptions of novice voters towards the election process, through the film "Kejarlah Janji". This research uses a qualitative approach with data collection techniques through in-depth interviews and analysis of the film "Kejarlah Janji". The research results show that first-time voters tend to have a limited understanding of the election process, but the film "Kejarlah Janji" is able to raise political awareness and motivate them to take part in the election.